Microstructure and creep rupture characteristics of an ultra-low carbon ferritic/martensitic heat-resistant steel - Yin, Feng-shi; Jung, Woo-sang; Chung, Soon-hyo (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
An ultra-low carbon ferritic/martensitic heat-resistant steel with 9.37Cr, 3.2W, 4.0Co, 0.22V, 0.09Nb, 0.068N and 0.007Ti (in mass%) was prepared. Nano-sized MX precipitates were found to distribute densely and homogeneously in the matrix within martensitic lath after normalizing-and-tempering heat treatment. During creep, Fe2W Laves phase was formed in the lath and grain boundaries. The oxide inclusions and coarse nitride particles were the crack initiation sites and their interfaces with matrix were the main propagation path of cracks. (c) 2007 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: STRENGTH